Brazilian cross-cultural adaptation of “Return-to-work self-efficacy” questionnaire - Silva Junior, João Silvestre; Griep, Rosane Härter; Lagerveld, Suzanne E; Fischer, Frida Marina (Revista de Saúde Pública, 2017)
OBJECTIVE To describe the translation and early stages of cross-cultural adaptation of the questionnaire Verwachtingen over werken (or “Return-to-work self-efficacy”) for workers in sick leave due to mental disorders, from the original in Dutch to the Brazilian Portuguese language. METHODS A panel gathering experts was formed to determine the questionnaire conceptual and item equivalence. For semantic equivalence, the Dutch-Portuguese Brazilian translations were consolidated and consensus meetings were held to structure versions of the instrument. Each version was back-translated from Brazilian Portuguese to Dutch and evaluated by one of the authors of the original version. The final version was submitted to two pre-tests for operational equivalence. RESULTS The original questionnaire in Dutch was translated twice to Brazilian Portuguese. During the process, four consensus meetings of the experts’ panel were performed to create the versions. Each version was back-translated to Dutch. One of the authors of the original questionnaire performed an evaluation on the first three versions until the definition of the final one, which was titled Expectativas sobre o trabalho (Expectations about work). Pre-tests’ participants did not reported problems to fill the questionnaire. CONCLUSIONS Results indicate that the Brazilian Portuguese cross-culturally adapted version maintains the original meaning of the questionnaire, while including characteristics peculiar to the Brazilian reality. Measurement and functional equivalence of this version must still be evaluated before its application can be recommended for workers who have been absent from work due to mental disorders.